Congenital portosystemic shunts in dogs - N. Kashliak; V. Vlizlo (Regulatory Mechanisms in Biosystems, 2025)
Congenital portosystemic shunt is one of the commonest congenital abnormalities in dogs. The objective of our study was to determine the presence of portosystemic shunts in the dogs using computed tomography, point out the typical symptoms and changes in the blood parameters that occur during this pathology. We analyzed nine patients with portosystemic shunts and nine clinically healthy dogs. Each group contained four Yorkshire Terriers, two Miniature Poodles, two Maltese dogs, and one mixed-breed dog. The animals were clinically examined, underwent computed tomography, and their blood was analyzed. Computed tomography revealed congenital portosystemic shunts in the dogs of small breeds aged six months to four years. Of the seven patients that underwent computed tomography, five were diagnosed extrahepatic portosystemic shunts (two M i niature Poodles, one mixed-breed dog, one Maltese dog, and one Yorkshire Terrier) and two were found to have intrahepatic portosystemic shunt (Yorkshire Terrier and Maltese dog). According to the results of computed tomography, we determined that the connection of the shunting vessel occurred through the gastric, splenic, azygos, and phrenic veins with the caudal vena cava. In the plasma of the patients with portosystemic shunts, the ammonia concentration was five times higher. Hyperamm o nemia was closely associated with the complexity of the portosystemic shunt and the severity of pathological process. The ill dogs were observed to have typical symptoms of damaged central nervous system – apathy, stupor, sopor, muscle tremor, hyperkinesias, and static and dynamic ataxia. The nervous symptoms and increase in the ammonia content in blood are the symptoms that warrant computed tomography to verify the diagnosis of portosystemic shunts. The patients had impaired fun c tions and the structure of the liver, especially notable in the parameters in blood serum, such as increased contents of total bile acids and bilirubin, reduced albumin content, and high activities of ALT, AST, and AP. Blood of a part of the ill dogs co n tained reduced contents of hemoglobin, number of erythrocytes, and hematocrit, increased contents of leukocytes and young forms of neutrophils, and also reduced number of platelets. In the future, we are going to analyze the efficacy of surgical trea t ment of dogs with portosystemic shunts.